Effects of layup configuration on the mechanical performance of variable stiffness laminated composites - Ong, Gerald Pan Hao (Nanyang Technological University, 2020)
In this project, conceptual design of composite laminates fully focuses on direct customization of the fibre layup configuration. Uni-directional, Symmetric & Cross-Ply and a variable Pattern 1 laminate were fabricated. These variable stiffness composite laminates will be undergoing mechanical tests which are in accordance to the American Society for Testing and Materials (ASTM) standards. For this investigation, the variable stiffness laminates were manufactured by both the automated fibre placement, AFP (G. Gardiner, 2019), using a KUKA Robot Machine (KR 240 R2900) and the hand layup method. Through experiments, the AFP process displayed a great potential for efﬁcient manufacturing of composite structures with high versatility, coupled with the decreasing labour with good control of fabricating parameters required. On the other hand, the hand layup method is seen to provide better surface finish but possess a reduction in the versatility of variable stiffness creation. Ultimately, the hand layup method offers a variation in stiffness of 5.16% to 6.10% while the AFP method has a stiffness variation of -19.95% and 18.24%. with the manufacturing thickness qualitative check done. Mechanical properties of different composite laminates were determined through testings and compared thereafter. Testings conducted show that uni-directional laminate is high in strength and stiffness. The other laminates had a range of 42.07% to 50.50% of the stress value of the uni-directional laminate. Pattern 1 has also been proven to be low in stiffness among all 3 different types of laminates tested. Nevertheless, pattern 1 also has the highest toughness as observed from the strain data obtained.